2013
DOI: 10.3109/10582452.2013.795640
|View full text |Cite
|
Sign up to set email alerts
|

Is Fibromyalgia Syndrome Common in the Patients with Primary Dysmenorrhea?

Abstract: Objective: To determine the association between fibromyalgia syndrome [FMS] and primary dysmenorrhea [PD]. Methods: Patients with PD formed the PD group and age-matched healthy normal controls were included in the HNC group. The new American College of Rheumatology FMS criteria were used in all patients and depression was assessed with the Beck Depression Inventory [BDI]. Results: There were 45 patients in the PD group and 45 patients in the HNC group. We found FMS in 15.6% of the PD patients and 0.0% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In one study, increased amplitude by CO2 laser evoked cerebral potential in these patients. 14 In the study by Soyupek et al, 17 the frequency of FM in primary dysmenorrhea was 15.6%. They observed that the somatic symptoms and symptom severity scores were higher in the patients with primary dysmenorrhea and FM compared to the PD patients without FM.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study, increased amplitude by CO2 laser evoked cerebral potential in these patients. 14 In the study by Soyupek et al, 17 the frequency of FM in primary dysmenorrhea was 15.6%. They observed that the somatic symptoms and symptom severity scores were higher in the patients with primary dysmenorrhea and FM compared to the PD patients without FM.…”
Section: Discussionmentioning
confidence: 97%
“…[11][12][13][14][15][16] There is a limited number of studies investigating a possible relationship between fibromyalgia and PMS and PD in the literature. 15,17 In this study, we aimed to investigate the presence of PMS, PD and depression among women with FM and healthy females and to determine possible factors related with PMS and PD in FM.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between primary dysmenorrhea and FMS is explored in a report from Disparta, Turkey (35). Both FMS and primary dysmenorrhea are chronic pain conditions.…”
Section: Mini International Neuropsychiatric Interview Depressiomentioning
confidence: 99%